Analitical Study of Vertical and Lateral Buckling on Pipeline Using Hobbs Method - Yoyok Setyo Hadiwidodo; Muhammad Makki Romadhoni; Herman Pratikno (International Journal of Offshore and Coastal Engineering (IJOCE), 2017)
During its operation, the pipeline will receive loads of internal pressure and thermal loads of fluid flowed until the pipes have both vertical and lateral buckling. Numerical analysis of vertical and lateral buckling Hobbs this method on a high friction coefficient and the coefficient of friction (0.3 ≤ φ ≤ 0.7) as well as the length of buckling as many as 20 variants were then performed comparisons, as well as axial tension comparison with DnV RP L110. So we get the relationship of temperature increase with the length and amplitude buckling. The data which is used is the gas pipeline Labuhan Maringgai-Muara Bekasi PT. Perusahaan Gas Negara (Persero) Tbk., Including the outer diameter of the pipe = 0.8128 m, plate thickness = 0.015875 m, thermal linear expansion coefficient = 11 x 10-6 m / oC, etc. So the higher coefficient of friction, temperature rise of 13.4%, 13.4% reduced buckling length, and axial tension increased to 12.95%. For the comparisons, the coefficient of friction does not affect the length of buckling on the vertical buckling. Comparison with DnV RP F110, increased coefficient of friction will increase the voltage axial (Seff) of 0.00024% and up 13.4% axial stress (P0) Hobbs.